Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Help with 2nd order differential equations needed

  1. Jan 27, 2006 #1
    I have come across the following question when revising for my upcoming exam, and wondered if anyone wouldn't mind giving me a hand and some hints as how to solve it.

    So far I have:

    [tex]F_{m} - k\frac{ds}{dt} = m\frac{d^2s}{dt^2}[/tex]

    And now I'm stuck as to the solution of the equation, as its a 2nd order non-homogenous differential equation, but doesn't have a term in s. Is this a problem when solving this, or do I just put it =0?

    Any hints would be appreciated!

    Apologies if the symbols don't come out as anticipated. Its my first time using them!
  2. jcsd
  3. Jan 27, 2006 #2


    User Avatar
    Homework Helper

    Make the substitution,

    [tex]v(t)=\frac{ds}{dt}\mbox{ so that }\frac{dv}{dt}=\frac{d^2s}{dt^2}[/tex]

    and the DE becomes a first order, namely

    [tex]F_{m} - kv = m\frac{dv}{dt},[/tex]

    that you can solve. Once you have a solution for v, plug it into [tex]v(t)=\frac{ds}{dt},[/tex] and that'll give you the solution to the given DE. Note that we didn't turn a second order DE into a first order DE, but rather a system of 2 first order DEs.
  4. Jan 27, 2006 #3
    That thought had occured to me, however the answer I got for v made no sense.

    I ended up with the following processes:

    [tex]f_{m} - kv = m\frac{dv}{dt}[/tex]
    [tex]\int dt = m\int\frac{dv}{F_{m} - kv}[/tex]
    [tex]t=\frac{-m}{k} \ln(F_{m} - kv) + c[/tex]

    which I then rearranged to make v the subject. However I don't think that this is correct way to do this is it? I think I probably used the wrong technique when integrating?
  5. Jan 27, 2006 #4


    User Avatar
    Homework Helper

    Here it goes...

    Rearrange the DE to be

    [tex]\frac{dv}{dt}+\frac{k}{m}v =\frac{f_{m}}{m} [/tex]

    Then the associated homogeneous equation is

    [tex]\frac{dv}{dt}+\frac{k}{m}v =0,[/tex]

    Put [tex]v(t)=Ae^{\lambda t}\mbox{ so that }\frac{dv}{dt}=A\lambda e^{\lambda t}[/tex] and this, when substituted into the homo. eqn., gives

    [tex]A\lambda e^{\lambda t}+\frac{k}{m}Ae^{\lambda t} =0[/tex]

    or [tex]Ae^{\lambda t}\left( \lambda +\frac{k}{m}\right) =0[/tex]

    and since [itex]e^{\lambda t}\neq 0[/itex] for any t, we have

    [tex]\lambda +\frac{k}{m} =0\mbox{ and hence }\lambda =-\frac{k}{m}[/tex]

    which gives [tex]v_H(t)=Ae^{-\frac{k}{m}t}[/tex] as the general solution to the associated homogeneous equation.

    Now, since the non-homogeneous equation, namely

    [tex]\frac{dv}{dt}+\frac{k}{m}v =\frac{f_{m}}{m},[/tex]

    differs only by a constant term, let us solve for an arbitrary constant as a particular solution, say [tex]v_P(t)=B[/tex], whose derivative is 0, and it must satisfy

    [tex]0+\frac{k}{m}B =\frac{f_{m}}{m},[/tex]

    so [tex]B =\frac{f_{m}}{k}=v_P(t),[/tex] and hence the most general solution to the given DE (the one in v) is [tex]v(t)=v_H(t)+v_P(t)[/tex], that is

    [tex]v(t)=Ae^{-\frac{k}{m}t} + \frac{f_{m}}{k},[/tex]

    The initial condition is v(0) = 0, from which we can determine A:

    [tex]v(0)=A\cdot 1 + \frac{f_{m}}{k}\Rightarrow A=-\frac{f_{m}}{k}.[/tex]

    Thus the solution for v is

    [tex]v(t)=-\frac{f_{m}}{k}e^{-\frac{k}{m}t} + \frac{f_{m}}{k}=-\frac{f_{m}}{k}\left( e^{-\frac{k}{m}t}-1\right)[/tex]

    but recall we had made the substitution


  6. Jan 27, 2006 #5
    Thank you. That helped a lot. I think I actually was on the right lines, I'd just confused myself, but your way seems to make a lot more sense to me.

    Thanks again
  7. Jan 27, 2006 #6


    User Avatar
    Homework Helper

    The above way is only so lengthy as I explained the means by which the technique is derived...

    Note that from

    [tex]t=\frac{-m}{k} \ln(F_{m} - kv) + c[/tex]
    [tex]-\frac{k}{m}t-c= \ln(F_{m} - kv) [/tex]
    [tex]v(t)=\frac{F_{m}}{k}-\frac{1}{k}e^{-\frac{k}{m}t-c} =\frac{F_{m}}{k}-\frac{1}{k}e^{-\frac{k}{m}t}e^{-c}[/tex]

    and then reason that [tex]e^{-c}=A[/tex] for some positive A... same answer as mine, if you follow it out.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook